Process to Remove the Size Variants Contained in the Antibody-Chelator Complex PCTA-NCAB001 for Radiolabeling with Copper-64 - Yukie Yoshii; Hiroki Matsumoto; Chika Igarashi; Tomoko Tachibana; Fukiko Hihara; Mitsuhiro Shinada; Atsuo Waki; Sei Yoshida; Kenichiro Naito; Kimiteru Ito; Tatsuya Higashi; Hiroaki Kurihara; et al. (MDPI AG, 2023)
Understanding the physicochemical properties of antibody-drug conjugates is critical to assess their quality at manufacturing and monitor them during subsequent storage. For radiometal-antibody complexes, it is important to control the properties of the antibody-chelator conjugate to maintain the quality of the final product. We have been developing 64Cu-labeled anti-epidermal growth factor receptor antibody NCAB001 (64Cu-NCAB001) for the early diagnosis and therapy of pancreatic cancer with positron-emission tomography. Here, we characterized the larger size variants contained in the antibody-chelator conjugate PCTA-NCAB001 by multi-angle light scattering coupled with size-exclusion chromatography. Secondly, we developed a chromatographic method to remove these size variants. Lastly, we demonstrated the stability of PCTA-NCAB001 after the removal of size variants. Dimer and oligomers were identified in PCTA-NCAB001. These larger size variants, together with some smaller size variants, could be removed by hydrophobic interaction chromatography. The PCTA-NCAB001 product, after the removal of these size variants, could be stored at 4 °C for six months. The methods developed here can be applied to assure the quality of PCTA-NCAB001 and other antibody-drug conjugates to facilitate the development of antibody-radiometal conjugates for positron-emission tomography and radioimmunotherapy of malignant cancers.